2012
DOI: 10.1111/j.1540-8167.2011.02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Electrical and Structural Remodeling Associated with Longstanding Pulmonary Hypertension and Right Ventricular Hypertrophy in Humans

Abstract: Idiopathic PH is associated with RA remodeling characterized by: generalized conduction slowing with marked regional abnormalities; reduced tissue voltage; and regions of electrical silence. These changes provide important insights into the isolated effects of PH fundamental to a range of clinical conditions associated with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 43 publications
(70 reference statements)
4
75
1
1
Order By: Relevance
“…This circuit is dependent on conduction across an isthmus of tissue between the tricuspid valve and inferior vena cava which can be safely and easily ablated with radiofrequecy catheter ablation [29]. This treatment is highly effective in the general population and studies in PAH patients have also shown high rates of success with a 100% acute success rate and approximately 75% long term success rate [7,8,21,30].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This circuit is dependent on conduction across an isthmus of tissue between the tricuspid valve and inferior vena cava which can be safely and easily ablated with radiofrequecy catheter ablation [29]. This treatment is highly effective in the general population and studies in PAH patients have also shown high rates of success with a 100% acute success rate and approximately 75% long term success rate [7,8,21,30].…”
Section: Reviewmentioning
confidence: 99%
“…In addition to structural remodelling electrophysiological assessment of a population of patients with PAH but no evidence of arrhythmias has shown slowing of conduction in the right atrium. These changes may provide the substrate necessary for the maintenance of atrial flutter [21].…”
Section: Reviewmentioning
confidence: 99%
“…Consistent with this concept, SAN dysfunction has been demonstrated in association with conditions leading to RA pressure and volume overload, including dyssynchronous AV pacing, pulmonary hypertension and chronic atrial septal defect. 57- 59 In a canine model of HF, cellular electrical remodeling was seen with downregulation of HCN channels in the SAN, lead- 54 ) However, there is conduction block of atrial tachyarrhythmia into the SAN, which may impart heterogeneity on the degree of remodeling that occurs (F). During atrial pacing at a cycle length of 200 ms (green line), the SAN is activated at 600 ms (blue line; OAPs, optical action potentials).…”
Section: Snd In Endurance Athletesmentioning
confidence: 99%
“…Chronically elevated right atrial pressure causes its remodeling and promotes supraventricular arrhythmias [1] -a factor of worse prognosis in this group [2].…”
Section: Balloon Atrial Septostomy In Pulmonarymentioning
confidence: 99%